1970
DOI: 10.3329/jdmc.v20i1.8563
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Serum Uric Acid Level And Essential Hypertension Among Patients Without Metabolic Syndrome

Abstract: Objective: To find out and asses the association between hyperuricaemia and hypertension. Methods: A case control study conducted in hypertension clinic, medicine and cardiac outpatient department of DMCH from December 2009 to November 2010 to evaluate association of hyperuricaemia and essential hypertension. A total of 51 hypertensive subjects aged 30 years and above were included as cases with same number of age & sex matched normotensive subjects as control after excluding metabolic syndrome, renal impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
2
1
Order By: Relevance
“…Our results were similar to the several other studies. [20][21][22][23][24][25] In favour of our study Assob JCN et al observed that the serum uric acid level in prehypertensive group was significantly higher than control group (p<0.0001) and SUA was found to be positively correlated with SBP and DBP (p<0.0001). 26 In contrast to our study, Hamdani IHAL observed no significant difference in serum uric acid level between hypertensive patients and control group.…”
Section: Discussioncontrasting
confidence: 35%
“…Our results were similar to the several other studies. [20][21][22][23][24][25] In favour of our study Assob JCN et al observed that the serum uric acid level in prehypertensive group was significantly higher than control group (p<0.0001) and SUA was found to be positively correlated with SBP and DBP (p<0.0001). 26 In contrast to our study, Hamdani IHAL observed no significant difference in serum uric acid level between hypertensive patients and control group.…”
Section: Discussioncontrasting
confidence: 35%
“…[4][5][6][7][8][9] In a previous study in Bangladesh, the observed prevalence of hyperuricemia in hypertensive and normotensive subjects were 25.4% and 9.8%, respectively. 29 In the present study, hyperuricemia was observed in 29.7% of hypertensive patients and 6.0% of normotensive controls, which was similar to most of the studies dine in this part of the world. The mean serum uric acid level was higher in the hypertensive patients than the normotensive controls in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Previous researchers had similar observations. [4][5][6][7][8][9]29 Among the hypertensive subjects of the current study, those with stage II HTN had significantly higher uric acid than those with stage I HTN. The higher uric acid levels with higher stages of HTN were also described by Neki et al, and Meti et al 8,19 Moreover, both the systolic and diastolic BP had significant positive correlations with serum uric acid levels in the hypertensive subjects of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study shows 33% population with hypertension had high serum uric acid level 21 . A study of our country observed 25.4% of study populations had hyperuricemia with hypertension 20 . In the present study it was revealed that serum creatinine was (p=0.752) not associated with serum uric acid level and did not agree with Nishida 6 .…”
Section: Discussionmentioning
confidence: 78%